Mitoxantrone ability to induce premature senescence in human dental pulp stem cells and human dermal fibroblasts - Seifrtova, M; Havelek, R; Soukup, T; Filipova, A; Mokry, J; Rezacova, M (Journal of physiology and pharmacology, 2013)
UNLABELLED: In this study we assessed the effects of the frequently used chemotherapeutic agent mitoxantrone (MTX) on dental pulp stem cells (DPSCs) and compared it with the response of human dermal fibroblasts (HDFs). DPSCs are valuable source of mesenchymal stem cells which may be extremely useful in a number of clinical applications. It is evident that both normal and tumor cells are being affected during therapy and characterization of these cells under genotoxic stress contributes to the evaluation of their safety usage. In the experiment cells were exposed to doses 5-150 nmol/l MTX. Proliferation of cells was detected by Z2 counter and viability by Vi-Cell XR using Trypan blue exclusion staining. Cell cycle analysis was determinated by flow cytometry, induction of apoptosis by monitoring the activities of caspases. The expression of key proteins was detected by Western blotting. Senescence was analyzed by activity of β-galactosidase and by detection of persisting DSBs-associated γH2AX foci. Exposure of both cell types to lower concentrations of MTX resulted in premature senescence (SIPS), which was accompanied with typical morphological changes, increased activity of senescence-associated β-galactosidase, persisting DSBs-associated γH2AX foci and cell cycle arrest in G2 phase. MTX provokes the activation of p53-p21(WAF1/Cip1) pathway in both cell types and activates cell-cycle inhibitor p16(INK4a) in HDFs, but not in DPSCs. Higher concentrations of MTX induced caspase-mediated apoptosis. CONCLUSIONS: MTX induces apoptosis or SIPS in both cell types in dependency on MTX doses. Both pathways prevent the proliferation of cells with damaged DNA.
Keywords: kůže; mitoxantron; mužské pohlaví; Topoisomerase II Inhibitors; Dental Pulp; inhibitory topoisomerasy II; kmenové buňky; Antineoplastic Agents; kaspasy; Humans; proliferace buněk; protinádorové látky; lidé; Cell Survival; Cells, Cultured; DNA Damage; Cell Proliferation; buněčný cyklus; Mitoxantrone; kultivované buňky; fibroblasty; Stem Cells; Cell Cycle; poškození DNA; Fibroblasts; zubní dřeň; Male; Skin; viabilita buněk; apoptóza; Caspases; Apoptosis